Disclosure to HIV-seropositive children in rural Zambia - Shinya Tsuzuki; Naoko Ishikawa; Hideki Miyamoto; Christopher Dube; Nangana Kayama; Janet Watala; Albert Mwango (BMC, 2018)
Abstract Background Care of children living with HIV comprises various issues, some considered challenging. One of the challenging areas is the serostatus disclosure to HIV-positive children. This study describes the current situation of HIV disclosure among rural children in Zambia and examines the socio-demographic factors promoting disclosure. Methods We used a mixed method approach applying both quantitative and qualitative methods to obtain comprehensive picture of HIV serostatus disclosure for children. Data were collected in Mumbwa district, Zambia (2010-2012), included 57 clinical records of children older than 5 years old. We examined children's age, gender, and cohabitation status with their parents, caregivers' level of education and income, and the relation between children and caregivers. Logistic regression model was applied to examine associations between disclosure and socio-demographic characteristics. Semi-structured interviews with 50 caregivers and 22 HIV-positive children were conducted to qualitatively investigate attitude towards disclosure and support needed. Results Full disclosure was completed in 17 out of 57 (29.8%) patients. Median ages of patients in disclosed group and non-disclosed group were 10 and 9, respectively (IQR 8.0-13.0, 7.0-11.25). In univariate analyses, older age and male gender has positive relation to the completion of serostatus disclosure. In logistic regression models, cohabitation status with patients' mothers showed positive correlation to the completion of serostatus disclosure. In the interviews with caregivers, all caregivers said that disclosure of serostatus is a necessary process and good for their children, while actual serostatus disclosure rate was low. Conclusion Serostatus disclosure to HIV-seropositive children is not prevalent in Rural Zambia. Although further researches would be desirable, increased support to caregivers would be beneficial.